Colombia as an "Oceanic Medium Power": Analysis of Country Interactions within the Caribbean Basin Region - Urrego-González, Felipe; Correa-Ramos, Nicolás; Mendoza-Pérez, Cristhian (EFIM Ediciones, 2018)
In recent years, Colombia has grown as a protagonist in the realities of Latin America. The country is in a favorable geographical position because it is located in the northern corner of South America, which allows it to interact not only regionally with South America but also with Central America and the Caribbean. In addition, the recent peace agreement with an insurgent group and the power vacuum left by its demobilization have developed regional opportunities and threats not only at the national level, but also the impact of transnational criminal organizations at the regional level. Taking into account a constructivist approach to international security and following the concepts of “Regional Security Complex” (CSR) and “Medium Oceanic Power”, the present manuscript analyzes how the Colombian government has been interacting with other states in the Caribbean Watersheds Region to generate common security and defense conditions.